Comparison of physics, chemistry and biology teachers’ perceptions of nature of science and domains of science - Kaya, E; Erduran, S (Springer Nature, 2024)
The paper presents an empirical study on physics, chemistry, and biology teachers’ perceptions of nature of science (NOS) and domains of science. Family Resemblance Approach to NOS (FRA) was used as a theoretical framework and informed the data analysis approaches. FRA inherently considers both domain-general and domain-specific features of NOS, and thus, it is an appropriate framework to address the main research problem about different subject teachers’ perceptions of NOS. Using quantitative and qualitative methods, we trace how the teachers perceive different aspects of NOS including scientific knowledge and practices. Although the teachers’ gender, teaching experience, and education level do not contribute to any variation in their perceptions of NOS, their subject-matter specialisms influence how they view different aspects of NOS. This observation is corroborated through some of the findings from the qualitative data analysis which provides detailed variations among the teachers indicating a complex set of relations between the similarities and differences among teachers’ perceptions across subject specialisms. Future research can extend the methodological approaches utilised in this paper to include, for example, in-depth interviews to explicate further the nuances across the subject teachers’ views of NOS in relation to domains of science.